Rethinking chronic pain: a dissociative framework for psychodynamic practice - Ho, Tim; Ryan, Mark; Dong, Skye (Frontiers in Psychology, 2025)
Chronic pain is increasingly recognised not only as a disorder of sensory processing but also as a disruption of self-experience. This article advances the concept of stimulus entrapment as a dissociative analogue in chronic pain, where consciousness becomes trapped in overwhelming bodily sensation, narrowing attention and preventing integration into coherent narrative or identity. This entrapment parallels dissociative states in trauma, where overwhelming affect fragments continuity of self. We argue that in chronic pain the “pain self” is often rejected and disowned, creating a split between the embodied, suffering self and the socially presented self. Such fragmentation amplifies distress, sustains alienation from the body, and fosters maladaptive coping. Conceptually, this framework links chronic pain to psychodynamic and dissociation theories, situating persistent pain as a disorder of disrupted self-integration. Framing chronic pain in this way clarifies why biomedical interventions alone often fail to restore function, since the problem lies not only in nociceptive signalling but also in fragmentation of selfhood. Psychodynamic approaches that emphasise narrative repair, emotional attunement, and restoration of self-coherence may reintegrate the “pain self” into the broader self-system, reduce alienation, and restore agency. We propose that stimulus entrapment offers a unifying conceptual bridge between chronic pain, trauma, and dissociation, opening new avenues for therapeutic engagement and future research.